AKUNTANSI SYA - Sari, Nurma (Khatulistiwa, 2014)
Accounting has, in fact, been around since the days of the Prophet and already existed in the Qur'an. It began with a transaction that was not made in cash or accounts receivable which required a careful and systematic bookkeeping. Accounting principles have embodied the conservative, historical, and material principles. The Sharia accounting principles are rules of common decision derived from the objective of financial reporting and the Sharia accounting concept which governs the development of Sharia accounting techniques. In practice, the principles are full disclosure principle, consistency principle, accrual basic principle, and the principle of current exchange rates.